Towards 2030: Shortcomings and Solutions in Food Loss and Waste Reduction Policy - Emily Friedman (Washington University Journal of Law & Policy, 2017)
This Note analyses the growing problems with food consumption and waste with regard to issues of hunger and environmental repercussions. Friedman first analyses the global food waste problem and how U.S. policies may be adding to the problem within the country. The Author relates these U.S. policies to those promulgated by the United Nations, those in Europe, and those at state and local levels. The Note argues the best approach toward addressing these problems will be a dual federal and state/local policy approach, including such methods as broadening USDA policies on grades and standards, creating tax incentives, and diverting local food waste from landfills.
Keywords: Agriculture; Agricultural Policy; United States Department of Agriculture; State and Local Government; Food Waste; Food Labeling; Federal Law; Federal Tax Incentives; Sustainable Development; United Nations; Poverty; Emerson Act